2006
DOI: 10.1177/030802260606900302
|View full text |Cite
|
Sign up to set email alerts
|

The Prevocational and Early Employment Needs of Adolescents with Juvenile Idiopathic Arthritis: The Adolescent Perspective

Abstract: The purpose of this study was to explore the prevocational needs of adolescents with juvenile idiopathic arthritis (JIA) from their own perspectives. A focus group discussion was undertaken with eight adolescents with JIA (14.2–16.6 years) attending one United Kingdom hospital. The topics of interest were (i) attitudes towards education, prevocational readiness and employment in relation to JIA; (ii) perceived barriers; (iii) coping strategies; and (iv) preferred sources of support. The data were analysed acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 28 publications
2
27
0
Order By: Relevance
“…Involvement in paid work can be complex for young adults, ages 18–30 years, who live with rheumatic diseases. During this period of life, they must learn to independently manage their health while also participating in a range of new responsibilities, such as finding employment, marriage, or parenting . Yet, research examining the work experiences of young adults with rheumatic diseases is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Involvement in paid work can be complex for young adults, ages 18–30 years, who live with rheumatic diseases. During this period of life, they must learn to independently manage their health while also participating in a range of new responsibilities, such as finding employment, marriage, or parenting . Yet, research examining the work experiences of young adults with rheumatic diseases is limited.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the participants expressed the desire for being addressed as a normal adolescent and not as a patient. That was often the reason for not disclosing having JIA to new classmates or colleagues (quotations [17][18][19]. Despite the variable course of the disease, having JIA had become the normfor most of the participants, especially for those who had been diagnosed with JIA in early childhood or multiple years ago (quotation 20).…”
Section: Normalitymentioning
confidence: 99%
“…To reach vocational adaptability, vocational support is important but rated far from satisfactory by adolescents with JIA [19]. Low expectations from others and limited career advice are seen as important barriers during career development [19]. We hypothesized that these barriers in the early career of JIA patients could be avoided, if proper support would be available.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported increased unemployment in young adults with JIA,11 12 22 which is not always related to disability or educational achievement. The importance and/or relevance of other markers of vocational readiness have been reported and include the lower expectations of professionals 27. How vocational aspects of transition are addressed within rheumatology remains unclear, particularly as significant unmet training needs in occupational therapists – the professionals most likely to implement vocational strategies – have been reported 28…”
Section: Evidence Of Needmentioning
confidence: 99%